2022
DOI: 10.1021/acscatal.2c02177
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2-to-Formate Conversion Driven by Visible Light over a Precious-Metal-Free Nonporous Coordination Polymer

Abstract: Metal−organic frameworks (MOFs) and coordination polymers (CPs) are potential candidates for high-performance photocatalysts because of their high tunability of electronic and structural properties. For example, MOFs and CPs having a high specific surface area (∼1000 m 2 g −1 ) have been applied as visible-light-driven photocatalysts for CO 2 reduction and water splitting. Herein, we show a unique CP possessing a metal−sulfur bond with Pb 2+ , an earth-abundant metal ion. Different from ordinary high-surface-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Currently, there have been numerous reports on transforming CO 2 into high-value-added products, mainly in the fields of photochemical products, fine chemical products, and polymeric materials. Among the many chemicals prepared from CO 2 , the preparation of cyclic carbonates is one of the most promising ways to achieve industrial application prospects for the utilization of CO 2 . Due to the advantages of high boiling point, large polarity, stable properties, safety, and nontoxicity, cyclic carbonates have very wide applications, such as intermediates of fine chemical products, polar aprotic solvents, lithium-ion battery electrolytes, and so on. To date, many heterogeneous and homogeneous catalysts have successfully been applied to the synthesis of cyclic carbonates, mainly including common organic small molecules (ionic liquids, organic bases, etc. ), metal oxides or salts, MOFs, COFs, and so on .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there have been numerous reports on transforming CO 2 into high-value-added products, mainly in the fields of photochemical products, fine chemical products, and polymeric materials. Among the many chemicals prepared from CO 2 , the preparation of cyclic carbonates is one of the most promising ways to achieve industrial application prospects for the utilization of CO 2 . Due to the advantages of high boiling point, large polarity, stable properties, safety, and nontoxicity, cyclic carbonates have very wide applications, such as intermediates of fine chemical products, polar aprotic solvents, lithium-ion battery electrolytes, and so on. To date, many heterogeneous and homogeneous catalysts have successfully been applied to the synthesis of cyclic carbonates, mainly including common organic small molecules (ionic liquids, organic bases, etc. ), metal oxides or salts, MOFs, COFs, and so on .…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka, Maeda and co-workers reported the CO 2 photoreduction using nonporous coordination polymer (CP) made with Pb 2+ cations linked by 1,3,4-thiadiazole-2,5-dithiol, named KGF-9, and containing a (−Pb−S−) n infinite structure. 39 KGF-9 presented a very small surface area of 0.7 m 2 /g. Using a solution of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole (BIH) in dimethyl sulfoxide (DMSO) under 370− 500 nm light irradiation, KGF-9 allowed reaching a HCOOH productivity of 1.15 mmol HCOOH /g cat /h.…”
Section: Doping Amino-mof With Transition Metal Aggregates (Ma)mentioning
confidence: 95%
“…Tanaka, Maeda and co-workers reported the CO 2 photoreduction using nonporous coordination polymer (CP) made with Pb 2+ cations linked by 1,3,4-thiadiazole-2,5-dithiol, named KGF-9, and containing a (−Pb–S−) n infinite structure . KGF-9 presented a very small surface area of 0.7 m 2 /g.…”
Section: Mof Photocatalysts With Pure Organic Linkersmentioning
confidence: 99%
“…Notably, in the present KGF‐10 CO 2 photoreduction system, the AQY value reached 9.8 % at 400 nm. We have recently reported that another MOF‐type material possessing a Pb−S bond (called KGF‐9) can reduce CO 2 to HCOO − with an AQY of 2.6 % at 400 nm, [13b] which was the highest AQY reported for a precious‐metal‐free single component photocatalyst towards CO 2 conversion into HCOO − . In the present work, better performance (9.8 % AQY) was obtained using Earth‐abundant Sn II ‐based MOFs that do not contain toxic Pb.…”
Section: Figurementioning
confidence: 98%